2013
DOI: 10.1017/s0003581513000279
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Bodies unto Waters: A Late Bronze Age Mid-Stream Midden Settlement and Iron Age Ritual Complex in the Fens

Abstract: This paper describes a Late Bronze Age midden settlement and a later Iron Age ritual complex on Godwin Ridge, a sand ridge that formerly lay mid-stream within the lower reaches of the River Great Ouse, in the Cambridgeshire fens. Numerous ritual deposits and significant quantities of human remains were recovered; some of the latter show signs of having been modified or dismembered. The ritual focus of the ridge was a riverside platform; associated with this was an important assemblage of wetland bird bone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Pelican bones are only positively identified as Dalmatian Pelican from four British sites through taxonomic assessment of diagnostic characters (Burwell Fen, Glastonbury Lake Village, Godwin Ridge, Haddenham V), with other specimens only identified to genus level (Forbes et al . 1958, Evans & Hodder 2006, Evans 2013). No specimens are directly dated, and the ages of pelican specimens from all British sites are poorly constrained (Table 1).…”
Section: Dalmatian Pelican Spatiotemporal Distribution In Britainmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelican bones are only positively identified as Dalmatian Pelican from four British sites through taxonomic assessment of diagnostic characters (Burwell Fen, Glastonbury Lake Village, Godwin Ridge, Haddenham V), with other specimens only identified to genus level (Forbes et al . 1958, Evans & Hodder 2006, Evans 2013). No specimens are directly dated, and the ages of pelican specimens from all British sites are poorly constrained (Table 1).…”
Section: Dalmatian Pelican Spatiotemporal Distribution In Britainmentioning
confidence: 99%
“…The existence and dynamics of such practices are almost certainly impossible to reconstruct or even identify in the archaeological record, further challenging our ability to understand whether direct human pressures drove regional pelican extinction. Evans (2013) provided the intriguing suggestion that pelicans (along with other birds including coots, ducks, geese, buzzards, cormorants, herons and corvids) might have been sacrificed at a Romano‐Celtic shrine at Haddenham, possibly performing a role as ‘winged messengers’ and/or used for entrail augury, and being equivalent in terms of ‘sacrifice’ size to a lamb or sheep. Serjeantson (2006) reported that many of the pelican bones from Haddenham exhibited cut‐marks and evidence of butchery indicative of feather removal and possible consumption, and suggested that pelicans might have been primarily hunted in Britain for trade in feathers (with their meat potentially fed to dogs rather than eaten by people).…”
Section: Pelican Extinction Dynamicsmentioning
confidence: 99%